مستجدات الكوارث في الطهارة (أندونيسيا خصوصًا) - Harman bin Tajang Mappa Bugis (البصيرة: مجلة الدراسات الإسلامية, 2024)
The main purpose of this study is to examine several cases and problems of taharah (purity) that occur during disasters as something that can never be separated from human life, and will last until the doomsday. The catastrophic phenomenon gave birth to various cases related to fiqh (Islamic law) that needed answers, so that a Muslim could take a science-based stance. The limitations of this study are: first, the urgency of disaster jurisprudence assessment, and second, the application of disaster jurisprudence assessment in Indonesia in taharah cases. This research uses methods that are inductive and analytical. This study aims to explain some cases of disaster jurisprudence in the taharah chapter. This research is expected to be a reference for disaster victims, volunteers, and the community in general. This study succeeded in formulating a definition of disaster and several conclusions of Islamic law in contemporary cases related to taharah; Among them are the law of preparing a special container of earth for use in tayammum, the law of ablution using water that is side by side or mixed with the corpse, the law of people who are unable to use all media for purification, The law uses flood water—especially if it has been mixed with mud—and the law uses mosques as shelters and temporary shelters for menstruating and postpartum women.